IoT Prototype Measuring Plant Height in Real-Time - Erkamim, Moh.; Wati, Vera; Priyadi, Sapto (JST (Jurnal Sains dan Teknologi), 2023)
Physically, development of plants will experience physical changes, one of which is the height of the plant. Monitoring activities will certainly be effective with the help of technology. The utilization of IoT is a technological breakthrough in that multitasking can be used for monitoring and sharing data simultaneously. So to support growth observation activities, this study aims to implement an IoT-based prototype modeling tool with ultrasonic sensors embedded in the NodeMCU microcontroller which is integrated with the database server. Modeling is used to analyze the workings of measuring plant height, involving case studies of mustard plant growth which are interpreted descriptively based on sensor capture height which is compared with expert-validated original observations. The research method used is quantitative data processing in the form of comparison charts. The data obtained in real-time by accessing the website address is available so that the data records are stored in the database server for as much as 1071 data for 33 days with 5 storage sessions a day. The results of the IoT prototype modeling managed to capture altitude data, with a comparison presentation between the height of the original plant and the sensor capture of 54.7% valid data without any difference. The conclusion from this study, there are still quite a lot of differences in the comparison of the two. This is due to modeling with improper sensor placement, so that it is detected outside the boundaries between predetermined objects.